The citizens, the politicians and the courts: A preliminary assessment of deliberative capacity in Colombia (2014)
What could deliberative politics offer a society that needs to strengthen its political regime and bring decades of violent confrontation to an end? By way of a preliminary answer, we argue that institutions and citizens that are more deliberative should reinforce each other, and reduce the impact of some of the factors that lead to violence. In this chapter, we first briefly outline the origins of the democracy deficit and the violence associated with the armed conflict, and also the current situation. The following two sections detail experiences of civic and institutional deliberation, and these provide an initial insight into what can generally be expected in terms of people’s behavior and disposition. Finally, we conclude with an idea of what a realistic deliberative democracy might look like in Colombia.